Mobile Apps to Reduce Tobacco, Alcohol, and Illicit Drug Use: Systematic Review of the First Decade - Staiger, Petra Karin; O'Donnell, Renee; Liknaitzky, Paul; Bush, Rachel; Milward, Joanna (JMIR Publications, 2020)
BackgroundMobile apps for problematic substance use have the potential to bypass common barriers to treatment seeking. Ten years following the release of the first app targeting problematic tobacco, alcohol, and illicit drug use, their effectiveness, use, and acceptability remains unclear. ObjectiveThis study aims to conduct a systematic literature review of trials evaluating mobile app interventions for problematic tobacco, alcohol, and illicit drug use. MethodsThe review was conducted according to recommended guidelines. Relevant databases were searched, and articles were included if the mobile app study was a controlled intervention trial and reported alcohol, tobacco, or illicit drug consumption as outcomes. ResultsA total of 20 studies met eligibility criteria across a range of substances: alcohol (n=11), tobacco (n=6), alcohol and tobacco (n=1), illicit drugs (n=1), and illicit drugs and alcohol (n=1). Samples included the general community, university students, and clinical patients. The analyzed intervention sample sizes ranged from 22 to 14,228, and content was considerably diverse, from simple stand-alone apps delivering self-monitoring or psychoeducation to multicomponent apps with interactive features and audio content, or used as adjuncts alongside face-to-face treatment. Intervention duration ranged from 1 to 35 weeks, with notifications ranging from none to multiple times per day. A total of 6 of the 20 app interventions reported significant reductions in substance use at post or follow-up compared with a comparison condition, with small to moderate effect sizes. Furthermore, two other app interventions reported significant reductions during the intervention but not at post treatment, and a third reported a significant interaction of two app intervention components. ConclusionsAlthough most app interventions were associated with reductions in problematic substance use, less than one-third were significantly better than the comparison conditions at post treatment. A total of 5 out of the 6 apps that reported intervention effects targeted alcohol (of those, one targeted alcohol and illicit drugs and another alcohol and tobacco) and 1 targeted tobacco. Moreover, 3 out of 6 apps included feedback (eg, personalized) and 2 had high risk of bias, 1 some risk, and 3 low risk. All 6 apps included interventions of 6 weeks or longer. Common study limitations were small sample sizes; risk of bias; lack of relevant details; and, in some cases, poorly balanced comparison conditions. Appropriately powered trials are required to understand which app interventions are most effective, length of engagement required, and subgroups most likely to benefit. In sum, evidence to date for the effectiveness of apps targeting problematic substance use is not compelling, although the heterogeneous comparison conditions and trial designs across studies limit the ability to compare efficacy between apps. We discuss potential approaches that can help ascertain whether the promise of mobile app interventions for problematic substance use can be fulfilled.